Simulated kangaroo care in very preterm infants does not reduce physiological instability: the COSYBABY randomised controlled cross-over trial - Hartley, Caroline; Adjei, Tricia; Chehrazi, Mohammad; Baticula, Joan; Andrzejewska, Izabela; Hyde, Matthew; Modi, Neena; Jeffries, Suzan (Frontiers in Pediatrics, 2025)
IntroductionInfants who are born very preterm experience frequent episodes of physiological instability including apnoea, oxygen desaturation and bradycardia due to immaturity of the pulmonary and nervous systems. Parental contact, such as kangaroo care, may reduce physiological instability. However, there may be long periods when parents cannot be with their baby. The BABYBE SYSTEM® is a medical device designed to simulate kangaroo care.MethodsWe conducted a randomised cross-over trial to determine whether episodes of apnoea and other episodes of physiological instability were reduced when infants were on an active BABYBE mattress. Each infant was included in the study for five consecutive days, with successive 12-h periods of the BABYBE® mattress being switched on or off. Episodes of physiological instability were identified from recordings of the vital signs monitors and compared with clinical notes. Generalised estimating equations models were used to compare physiological instability when the BABYBE mattress was switched on vs. off.ResultsA total of 23 infants born before 32 weeks' gestation were included in the main analysis. There was no significant difference between the number of apnoeic episodes infants experienced in the 12-h period when the BABYBE mattress was on compared with when the mattress was switched off (difference between conditions = 1.5 apnoeas, 95% CI: −0.2–3.2, p = 0.09). The number of episodes of apnoea identified from vital signs recordings were much higher than those documented in the clinical records (a total of 1,157 apnoeic episodes were identified across all infants from vital signs recordings compared with a total of 27 documented in clinical/nursing notes of the same infants).DiscussionThis trial does not provide evidence of a benefit of the BABYBE mattress for improving physiological stability in preterm infants. This study provides confirmation of the under-recognition of apnoeic episodes in clinical notes and the benefit of assessing electronic recordings of vital signs to gain a more complete picture of physiological stability.